The method of reducing heat loss from thermal bridges in residential buildings with internal insulation in the hot summer and cold winter zone of China - Zhao, Kang; Jiang, Ziling; Huang, Yixiong; Sun, Zhijian; Wang, Lujing; Gao, Weijun; Ge, Jian (Journal of Building Engineering, 2022)
The higher demands for energy efficiency in nearly zero energy buildings (nZEBs) give rise to concerns on the impact of thermal bridges on building's thermal performance. The extra heat loss by thermal bridges needs to be reduced especially for residential nZEBs with internal insulation in China's Hot Summer–Cold Winter (HSCW) zone. This paper defines and compared four typical types of thermal bridges based on their constructional and thermal characteristics. A novel multi-objective optimization method for determining the best construction to improve thermal bridges is also proposed. The heat loss through thermal bridges was estimated through the linear thermal transmittance using COMSOL Multiphysics software. Optimization of design parameters was carried out by Pareto-based multi-objective optimization tool in Python, while heat loss reductions and quantities of material have been comprehensively considered. Corresponding suggested values for design parameters of each thermal bridge type have been put forward. Results obtained by a case study of a typical residential nZEB under various thermal bridge conditions and different air-conditioning patterns also highlight the importance of insulation design of envelope considering the influence of thermal bridge, where the proportion that on annual heating and cooling loads can be reduced from 1.7%-8.2% to 0.4%–2.5%. •Definition and comparation of thermal bridges' impacts on heat loss.•Proposed thermal bridge improvement methods for each type of junction.•Multi-objective optimization for both energy efficiency and material saving.•Energy performance in a residential nZEB considering effects of thermal bridges.